Reducing greenhouse gas emissions and improving air quality : two interrelated global challenges - Erickson, L. E. (Larry Eugene), 1938-; Brase, Gary (CRC Press, 2019)
The world's atmosphere is a common resource. Air quality, along with energy, transportation, and climate change have significant impacts on our lives and this book helps readers understand the changes happening at the nexus of these areas, as they relate to reducing greenhouse gas emissions and improving air quality. Discussing the transitions to electric vehicles, solar and wind energy for electricity generation, battery developments, smart grids and electric power management, and progress in the electrification of agricultural technology, it also provides the latest information in the context of the United Nations sustainable development goals and the Paris Agreement on Climate Change. Features: Includes content on how to improve urban air quality in large cities and urban environments. Effectively addresses the nexus of energy, transportation, air quality, climate change and health. Discusses innovative concepts at the nexus of renewable energy, smart grid, electric vehicles, and electric power management. Describes recent progress in meeting the goals of the Paris Agreement on Climate Change and the benefits of reducing greenhouse gas emissions. Written for a wide audience by world experts in sustainability. Reducing Greenhouse Gas Emission and Improving Air Quality: Two Interrelated Global Challenges, is an invaluable book for professionals and academics at the center of changes relating to solar and wind energy, electric vehicles, and charging infrastructure, including government officials, community leaders, researchers, students, and interested citizens. It is also an excellent text for classes that address sustainability, particularly for those focused on transportation and energy.